Columnaristerol A, a novel 19-norsterol from the Formosan octocoral Nephthea columnaris. Issue 20 (15th October 2016) - Whuang, Ta-Yuan; Tsai, Wen-Cheng; Chen, Nan-Fu; Chen, Zhi-Cheng; Tsui, Kuan-Hao; Wen, Zhi-Hong; Su, Yin-Di; Chang, Yu-Chia; Chen, Yu-Hsin; Lu, Mei-Chin; Fang, Lee-Shing; Chen, Jih-Jung; et al.
Graphical abstract: Abstract: Columnaristerol A (1 ), a rare natural 19-norsterol possessing a 10β-hydroxy group was isolated from the Formosan octocoral Nephthea columnaris, and its structure was elucidated by spectroscopic methods. Sterol1 was found to be a cytotoxic agent that exhibited in vitro moderate cytotoxic activity against MOLT-4 and SUP-T1 human leukemia–lymphoma cell lines.